Recognition cascade and metabolite transfer in a marine bacteria‐phytoplankton model system. (21st July 2017) - Durham, Bryndan P.; Dearth, Stephen P.; Sharma, Shalabh; Amin, Shady A.; Smith, Christa B.; Campagna, Shawn R.; Armbrust, E. Virginia; Moran, Mary Ann
Summary: The trophic linkage between marine bacteria and phytoplankton in the surface ocean is a key step in the global carbon cycle, with almost half of marine primary production transformed by heterotrophic bacterioplankton within hours to weeks of fixation. Early studies conceptualized this link as the passive addition and removal of organic compounds from a shared seawater reservoir. Here, we analysed transcript and intracellular metabolite patterns in a two‐member model system and found that the presence of a heterotrophic bacterium induced a potential recognition cascade in a marine phytoplankton species that parallels better‐understood vascular plant response systems. Bacterium Ruegeria pomeroyi DSS‐3 triggered differential expression of >80 genes in diatom Thalassiosira pseudonana CCMP1335 that are homologs to those used by plants to recognize external stimuli, including proteins putatively involved in leucine‐rich repeat recognition activity, second messenger production and protein kinase cascades. Co‐cultured diatoms also downregulated lipid biosynthesis genes and upregulated chitin metabolism genes. From differential expression of bacterial transporter systems, we hypothesize that nine diatom metabolites supported the majority of bacterial growth, among them sulfonates, sugar derivatives and organic nitrogen compounds. Similar recognition responses and metabolic linkages as observed in this model system may influence carbon transformations by ocean plankton.